Ka Band-pass Filter Based on SIW Technology for Wireless Communications - Mehdi Damou; Yassine Benallou; Mohammed Chetioui; Abdelhakim Boudkhil; Redouane Berber (Journal of Telecommunications and Information Technology, 2021)
The paper proposes a new third-order Chebyshev bandpass filter based on the substrate integrated waveguide (SIW) manufacturing technology using an inductive iris and a defected ground structure (DGS) station to resonate in the Ka frequency band, intended for wireless communication applications. All steps that are necessary for designing such a filter have been described in detail based on specific analytical equations harnessed to calculate the different synthesizable parameters of the proposed band-pass filter design, such as the coupling matrix, quality coefficients and initial geometric dimensions. The filter’s ideal frequency response is extracted from an equivalent circuit employing localized elements developed with the use of Design Microwave Office Software. Otherwise, HFSS is employed to set the initial parameters of the proposed topology that will not meet the target specifications defined previously. Accordingly, optimization procedures are necessary for different SIW band-pass filter parameters to reach a high frequency response for the proposed design. The detailed results presented show high efficiency of the SIW technology that offers good performance with lower filter volumes. Two topologies have been developed and then optimized to demonstrate the usefulness of EM software